2021
DOI: 10.11622/smedj.2019141
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward artificial intelligence in radiology with learner needs assessment within radiology residency programmes: a national multi-programme survey

Abstract: Online first papers have undergone full scientific review and copyediting, but have not been typeset or proofread. To cite this article, use the DOIs number provided. Mandatory typesetting and proofreading will commence with regular print and online publication of the online first papers of the SMJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 26 publications
(33 reference statements)
5
74
0
Order By: Relevance
“…Additionally, radiologists, radiology residents, medical students have increasingly recognized the need for a basic understanding of artificial intelligence. 4 , 5 , 6 Despite these impending changes, medical education designed for future radiologists have only recently begun. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, radiologists, radiology residents, medical students have increasingly recognized the need for a basic understanding of artificial intelligence. 4 , 5 , 6 Despite these impending changes, medical education designed for future radiologists have only recently begun. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…This implies that updated regulatory policies and continuing education of all users (including adequate information to patients about the purposes, rights, and legal terms related to the use of AI for their health management) should be promoted, as AI systems are poised to become more widely available, complex and powerful. To this purpose, it is noteworthy that the majority of Singaporean radiology residents joining a national multiprogram survey thought that since AI will drastically change radiology practice, AI/ML knowledge should be taught during residency (84.8% of survey participants), and this was as important as imaging physics and clinical skills/knowledge curricula (80.0 and 72.8%, respectively) ( Ooi et al, 2021 ). From a psychological standpoint, it has been observed that openness to experience is associated with higher trust toward robots and AI, as well as having a degree in technology or engineering, exposure to robots online, and robot use self-efficacy ( Oksanen et al, 2020 ), highlighting the importance of technology knowledge in addition to personal differences in building AI confidence.…”
Section: Artificial Intelligence and Humansmentioning
confidence: 99%
“…One survey showed that resident physicians and medical students desired AI-related training but that only a few had opportunities to participate in personal-level data science or machine learning courses. 60 Moreover, medical workers in less developed areas have great concerns about whether they will be replaced by AI in the future. 61 Possible solutions…”
Section: Societal Acceptancementioning
confidence: 99%